The use of minimal fluoroscopy for cardiac electrophysiology procedures: A meta‐analysis and review of the literature. Issue 6 (17th May 2021) - Chiang, Lorraine Lok Wing; Li, Christien; Hong, Kathryn L; Hui, Winsy Sin; Beh, Sze Yi; Gong, Mengqi; Liu, Tong; Li, Guangping; Xia, Yunlong; Ho, Jeffery; Roever, Leonardo; Duong, Sophia; et al.
Abstract: Background: Conventional catheter ablation involves prolonged exposure to ionizing radiation, potentially leading to detrimental health effects. Minimal fluoroscopy (MF) represents a safer alternative, which should be explored. Data on the safety and efficacy of this technique are limited. Hypothesis: Our hypothesis is that MF is of equal efficacy and safety to conventional catheter ablation with the use of fluoroscopy by performing a meta‐analysis of both randomized controlled trials (RCTs) and real‐world registry studies. Methods: Pubmed and Embase were searched from their inception to July 2020 for RCTs, cohort and observational studies that assessed the outcomes of catheter ablation using a MF technique versus the conventional approach. Results: Fifteen studies involving 3795 patients were included in this meta‐analysis. There was a significant reduction in fluoroscopy and procedural time with no difference in acute success (odds ratio [OR]:0.74, 95% CI: 0.50–1.10, p = .14), long‐term success (OR:0.92, 95% CI: 0.65–1.31, p = .38), arrhythmia recurrence (OR:1.24, 95% CI: 0.75–2.06, p = .97) or rate of complications. (OR:0.83, 95% CI: 0.46–1.48, p = .65). Additionally sub‐group analysis for those undergoing catheter ablation for atrial fibrillation (AF) did not demonstrate a difference in success or complication rates (OR:0.86, 95% CI: 0.30–2.42, p = .77). Multivariate meta‐regression did not identify the presence of moderator variables. Conclusion: This updated meta‐analysis demonstrated an overall reduction in procedural and fluoroscopy time for those undergoing a minimal fluoroscopic approach. There was no significant difference in either acute or chronic success rates or complications between a MF approach and conventional approach for the management of all arrhythmias including those undergoing catheter ablation for AF.